Dual nationality in the case law of the Court of Justice of the European Union - Dudrová, Kateřina; Grmelová, Nicole, 1975-; Hubková, Pavlína; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2014)
This work focuses on the case law of the Court of Justice of the European Union regarding dual nationality and the explanation of the characteristics of the terms related to this issue. It tries to facilitate the work with judicial decisions for readers and to help with their understanding by outlining the basic concepts. Furthermore, its effort is to analyse the chosen case law, compare the judgments with the opinions of the Advocates General and to try to find the certain evolution in decisions of the Court of Justice of the European Union. This would lead to the understanding of the fundamental points of dual nationality in the end.
Vedoucí práce: Nicole Grmelová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: podnikání a právo [obor bakal. práce]; bakalářské práce; bachelor's theses